Effects of cognitive and motor dual-tasks on oropharyngeal swallowing assessed with FEES in healthy individuals - Paul Muhle (Nature Portfolio, 2020)
Abstract Dysphagia is frequent in many neurological diseases and gives rise to severe complications such as malnutrition, dehydration and aspiration pneumonia. Therefore, early detection and management of dysphagia is essential and can reduce mortality. This study investigated the effect of cognitive and motor dual-task interference on swallowing in healthy participants, as dual-task effects are reported for other motor tasks such as gait and speech. 27 participants (17 females; 29.2 ± 4.1 years) were included in this prospective study and examined using flexible endoscopic evaluation of swallowing (FEES). Using a previously established FEES-based score, the paradigms “baseline swallowing”, “cognitive dual-task” and “motor dual-task” were assessed. Scores of the three paradigms were compared using a repetitive measures ANOVA and post-hoc analysis. Mean baseline swallowing score in single task was 5 ± 3. It worsened to 6 ± 5 in the cognitive (p = 0.118), and to 8 ± 5 in the motor dual-task condition (p < 0.001). This change was driven by subclinical worsening of premature bolus spillage and pharyngeal residue. Oropharyngeal swallowing is not exclusively reflexive in nature but requires attention, which leads to motor dual-task interference. This has potential diagnostic and therapeutic implications, e.g. in the early screening for dysphagia or in avoiding dual-task situations while eating.